Utilizing the RE-AIM framework to determine effectiveness of a preschool intervention program on social-emotional outcomes. (April 2020) - Natale, Ruby A.; Kolomeyer, Ellen; Robleto, Ana; Jaffery, Zafreen; Spector, Rachel
Highlights: Using the RE-AIM model, our program reached 305 children from diverse racial and ethnic backgrounds. Social/emotional development scores significantly increased pre- to post-intervention, suggesting effectiveness . 73 childcare programs adopted our program into their setting. The program was implemented with fidelity and majority of families were satisfied with their participation. Gains were maintained ; most children were not receiving intervention, special education, or at risk for expulsion. Abstract: Social-emotional issues in preschoolers continue to be an area of concern across the nation. Models to determine effective implementation practices are needed. The Reach, Effectiveness, Adoption, Implementation, Maintenance (RE-AIM) framework is one model that can be used to evaluate program implementation in preschool settings. The Jump Start program provided short-term intervention to children in low-income preschools from multiethnic backgrounds. The goal was to promote prosocial behaviors while minimizing problem behaviors. Various evidenced-based practices (i.e., I Can Problem Solve, play therapy, Pyramid Model) were utilized. 305 children from 73 childcare centers participated in the program. The majority of participants were from ethnic minority backgrounds and resided in high-poverty areas of the county. The RE-AIM framework was utilized to determine program outcomes. Results showed successes on each level of RE-AIM with an at-risk population. The Jump Start program significantly increased positive behaviors and decreased challenging behaviors in preschool-aged children. Results indicated medium to large effect sizes. One year following program participation, the majority of children who participated in the program were at decreased risk of special education services and expulsion.